Contracting with Controllable Risk - Armstrong, Christopher S.; Glaeser, Stephen A.; Huang, Sterling (The Accounting Review, 2022)
ABSTRACT We examine how executives' ability to control their firms' exposure to risk affects the design of their incentive-compensation contracts. Our natural experimental evidence shows that exchange-traded weather derivatives allow executives to control their firms' exposure to weather risk. Once these derivatives became available, those executives who use them to hedge experience relative reductions in their total compensation and equity incentives. The decline in compensation is consistent with a reduction in the risk premium that executives receive for exposure to weather risk. The decline in equity incentives is consistent with the relation between risk and incentives shifting in a complementary direction when executives can better control their firms' exposure to risk. Collectively, our findings provide evidence that executives' ability to control their firms' exposure and, by extension, their own to an important source of risk influences the design of their incentive-compensation contracts. JEL Classifications: G32; J33; J41.